2010
DOI: 10.1002/masy.201000009
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on the NMR Chemical Shifts of Imidazolium‐Based Ionic Liquids and Cellulose Therein

Abstract: The interactions of ionic liquids (IL) with solvents usually used in liquid‐state nuclear magnetic resonance (NMR) spectroscopy are studied. The 1H‐ and 13C‐NMR chemical shift values of 1‐n‐butyl‐3‐methyl (BM)‐ and 1‐ethyl‐3‐methyl (EM)‐substituted imidazolium (IM) ‐chlorides (Cl) and ‐acetates (Ac) are determined before and after diluting with deuterated solvents (DMSO‐d6, D2O, CD3OD, and CDCl3). The dilution offers structural modifications of the IL due to the solvents capacity to ionization. For further inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 23 publications
8
34
0
Order By: Relevance
“…[4] They followed up this study by looking at the relaxation times of 13 C-and supposedly H-bonded 35/37 Cl nuclei involved in the dissolution process. [3] In 2010, Hesse-Ertelt et al [16] studied the effect of solvent concentration on the chemical shifts of imidazolium ionic liquidsa nd compared chemical shifts obtained from an HSQC spectrumo f [emim][OAc]a nd 10 wt %e ucalyptus pre-hydrolysis kraft( PHK) pulp diluted with [D 6 ]DMSO with those from solid-state NMR spectroscopy.H owever,t hey note the difficulty to obtain spectra of undiluted, neat samples and the problem of overlapping resonances with the [emim] + + cation.…”
Section: Introductionmentioning
confidence: 99%
“…[4] They followed up this study by looking at the relaxation times of 13 C-and supposedly H-bonded 35/37 Cl nuclei involved in the dissolution process. [3] In 2010, Hesse-Ertelt et al [16] studied the effect of solvent concentration on the chemical shifts of imidazolium ionic liquidsa nd compared chemical shifts obtained from an HSQC spectrumo f [emim][OAc]a nd 10 wt %e ucalyptus pre-hydrolysis kraft( PHK) pulp diluted with [D 6 ]DMSO with those from solid-state NMR spectroscopy.H owever,t hey note the difficulty to obtain spectra of undiluted, neat samples and the problem of overlapping resonances with the [emim] + + cation.…”
Section: Introductionmentioning
confidence: 99%
“…The upfield shift in δ is a direct consequence of weakening of the hydrogen bond between cations and anions and the interaction with solvent molecules. Figure shows that the δ value of the C‐2 proton is strongly affected by the polarity of the solvent, and it is reported that higher polarity leads to lower δ values of the C‐2 proton . In the case of [HmIm][CH 3 COO], we have explained the solvation of ions on the basis of the δ value of CH 3 ‐ proton of anions [CH 3 COO].…”
Section: Resultsmentioning
confidence: 86%
“…Figure 8s hows that the d value of the C-2 protoni ss trongly affected by the polarity of the solvent, and it is reported that higher polarity leads to lower d values of the C-2 proton. [38][39][40] In the case of [HmIm][CH 3 COO],w e have explained the solvation of ions on the basis of the d value of CH 3 -p roton of anions[ CH 3 COO].G iven that the N-H proton is more acidic than the C-2 protono fp rotic ionic liquids and that it resonates at am ore downfield position, we consider the CH 3 -p roton of the anion for analysis. The d value of the CH 3 -proton in D 2 O( 1.78 ppm) is lower than that in [D 6 ]DMSO (1.93 ppm).…”
Section: Solvation Effectsmentioning
confidence: 99%
“…EMIMAc was chosen because it dissolves cellulose and shows no chemical shifts in the region of 60-110 ppm, where the cellulose carbon signals appear. It has been reported that the solvent effect of DMSO on the chemical shifts of EMIMAc is minor (Hesse-Ertelt et al 2010). The chemical structures of cellulose and EMIMAc are shown in Fig.…”
Section: Characterisationmentioning
confidence: 96%